The Ryff’s Psychological Well-Being Scale for Indonesian Higher Education Students: A RASCH Model Analysis - Purnama, Diana Septi; Farozin, Muh; Astuti, Budi (Indonesian Research Journal in Education |IRJE|, 2022)
The research aimed to examine the Ryff’s six factors model of psychological well-being that could be applied to higher education students in Indonesia by using the RASCH model. 425 higher education students completed adapted scales to assess demographic variables. The results showed that the person separation criteria scored 2.38 in the poor category, the item separation scored 12.21 in the very good category, the person reliability scored 0.85 in the good category, and the item reliability scored 0.99 in the very good category. The subscales of the PWB-42 showed accepted levels of reliability and the validity of the psychological well-being scale. The terms of the person and item strata separated criteria in the RASCH model showed good results. However, the statement items provided are not broad enough to reveal the condition of psychological well-being. Therefore, future higher education students research should develop more specific and context-appropriate items for a better operationalization of the Ryff’s theoretical model.